Changing grain markets call for new storage practices - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Responsibility for the marketing and storage of maize is shifting from government-sponsored marketing boards to the private trading sector. This change has implications for producers, who may encounter new problems with the storage and marketing of...